Genomic characterization, in vitro, and preclinical evaluation of two microencapsulated lytic phages VB_ST_E15 and VB_ST_SPNIS2 against clinical multidrug-resistant Salmonella serovars - Reem A. Youssef; Masarra M. Sakr; Rania I. Shebl; Bishoy T. Saad; Khaled M. Aboshanab (BMC, 2024)
Abstract Background Salmonella infections continue to be one of the essential public health issues threatening millions of people. With the increasing occurrence of resistance against conventionally used antibiotics, the search for alternatives has become crucial. In this study, we aimed to isolate, characterize, and evaluate two lytic bacteriophages against clinically isolated multidrug-resistant (MDR) Salmonella serovars. Methods Screening for the phage lytic activity was performed using a spot test. Characterization of the isolated phages was done by determining the host range, longevity test, and the effect of temperature, pH, organic solvents, and morphological characterization using a transmission electron microscope. Genomic analysis was performed using Oxford nanopore sequencing. The lytic activities of the free phage lysates and formulated phage as microencapsulated were evaluated both in vitro and in vivo. Results Two phages (VB_ST_E15 and VB_ST_SPNIS2) were successfully isolated and showed lytic strong activities against MDR Salmonella (S.) Typhimurium ATCC 14,028, S. Paratyphi A, and S. Typhi. The two phages survived at the tested temperatures, maintained their infectivity for 90 days, and retained their activity until 60 °C with thermal inactivation at 65 °C. They were lytic at a pH range from 3 to 11 but lost their activities at extremely acidic or alkaline pH. The phages could withstand the organic solvents but were completely inactivated by 100% ethanol. Both phages were classified under the order Caudoviricetes, and Genus: Uetakevirus. Their genomic sequences were assembled, annotated, and submitted to the NCBI GenBank database (OR757455 and OR757456). The preclinical evaluation using the murine animal model revealed that the two-phage cocktail managed MDR Salmonella infection as evidenced by the reduction in the bacterial burden, increased animal weight, and histopathological examination. Conclusion The two encapsulated phage formulas could be considered promising candidates for the management of MDR Salmonella-associated infections and clinical analysis should be undertaken to evaluate their potential use in humans.